Surfactant degradative plasmids - Taranova, L.A.; Dybkova, S.N.; Grishchenkov, V.G.; Mordukhova, E.A.; Boronin, A.M. (Биополимеры и клетка, 2000)
It has been shown that the degradation of anionlc, cationic and ampholytic surfactants by pseudomonads can be controlled by the plasmids with size of 60–130 kb. Most plasmid strains that degrade surfactants are capable of conjugative transfer and elimination from bacteria cells. Restriction patterns of plasmids do not reveal significant homology between plasmids. Показано, что деградация многих анионных, катионных и амфолитных поверхностно-активных веществ у псевдомонад контролируется плазмидами размером 60–130 тыс. п. н. Большинство плазм ид способны к конъюгативному переносу и элиминации из бактериальных клеток. Полученные первичные рестрикционные карты данных плазм ид имеют значительные различия. Показано, що деградація багатьох аніонних, катіонних та амфолітних поверхнево-активних речовин (ПАР) у псевдомонад контролюються плазмідами розміром 60–130 тис. п. н. Більшість плазмід здатні до кон'югативного переносу та елімінації з бактеріальних клітин. Створені первинні рестрикційні карти плазмід біодеградації ПАР мають значну різницю.